Implikasi Perkembangan Teknologi Blockchain terhadap Keabsahan Alat Bukti Perkara Perdata - Dylla Melisa; Syuryani Syuryani (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of information technology has brought significant changes to various aspects of life, including business and law. One of the key innovations in this context is Blockchain technology. Blockchain has revolutionized information storage and exchange, particularly in the realm of Indonesian contract transactions. It is a decentralized technology that allows for transactions between two parties who do not trust each other, without the need for a third party. The data in Blockchain is stored across the entire network, ensuring that it cannot be altered by a single party without the agreement of the entire network. Furthermore, Blockchain enhances transparency and accountability in data management. This study employs a normative legal research method with a descriptive approach. The findings reveal that Blockchain technology has significant implications for the protection of personal data and the validity of evidence in civil cases. As the technology continues to evolve, its potential to transform legal transactions in Indonesia is undeniable.